The Relationship between Presentation of Online Self and Conscientiousness in Emerging Adults in India - Naomi Hegde; Priyal Sanghavi; Prachi Tanna (International Journal of Behavioral Sciences, 2025)
With the rise of social media use, understanding how individuals curate their online presence and experiment with different aspects of their digital identity is crucial in determining whether their online self is an extension of their offline identity or a distinct construct. This necessitates an examination of personality traits, particularly conscientiousness, to explore its role in online self-expression. Existing research suggests that individuals with high conscientiousness tend to maintain consistency between their online and offline identities (Authentic Self), are less likely to engage in varying self-presentations online (Adaptable Self), and experience greater restraint in expressing themselves freely in digital spaces (Freedom of Self Online). The aim of this study was to examine the relationship between conscientiousness and the three factors of online self-presentation—Authentic Self, Adaptable Self, and Freedom of Self Online—among emerging adults in India. The study administered the Presentation of Online Self Scale for Adults (POSSA; 2021) and the Concise Conscientiousness Measure-S (CCM-S; 28 items; 2021) to assess these variables among individuals aged 18–25 years (n = 116). The results indicated a significant positive correlation between conscientiousness and Authentic Self (r = 0.294, p < .01); and a significant negative correlation between conscientiousness and Freedom of Self Online (r = -0.225, p < .05). Moreover, a negative correlation was found between conscientiousness and Adaptable Self, however, it was not significant. Thus, it is likely that a relationship between conscientiousness and online self presentation exists, wherein individuals might consider their online identities as an extension of their offline self but might feel restricted in their online interactions.
Keywords: Conscientiousness; Correlation; Digital Identity; Emerging Adults; Presentation of Online Self